The effect of climate variability on dengue disease in endemic areas: a study of Bandung City, Indonesia: 10.55131/jphd/2025/230321 - Akbar, Hairil; Fikri, Dzil; Carles, Carles; Usa, WD. Yuni M; Natsir, Ramdhani M; Pratama, Reza; Sutriyawan, Agung (Journal of Public Health and Development, 2025)
Dengue fever remains a significant public health issue, particularly in dengue-endemic areas such as Bandung City, Indonesia. Climatic variations have been shown to influence the transmission and incidence of dengue, emphasizing the need to analyze these relationships in endemic regions. This study aimed to analyze the relationship between climate variability and dengue incidence in Bandung City during 2021–2023 and to project trends for 2024 and 2025. An ecological study design was used, with secondary data collected from 30 sub-districts. Climate variables (temperature, humidity, rainfall, wind speed, and air pressure) and dengue incidence data were analyzed using multiple linear regression and exponential smoothing. The results showed that climatic variations collectively explained 24.5% of the variance in dengue incidence (R²=0.245, p=0.018), with temperature (p=0.024, r=0.375) and air pressure (p=0.015, r=-0.402) being the most influential factors. Humidity, rainfall, and wind speed showed no significant individual effects. Projections indicated an increasing trend in dengue cases in 2024 and 2025, supported by preliminary data showing 1,741 cases reported in Bandung City as of March 2024.These findings confirm the relevance of climate variability as a predictor for dengue incidence. Environment-based interventions, including climate-based early warning systems, proper water reservoir management, community education, and cross-sectoral collaboration, are essential to mitigate the impact of climate variability on dengue transmission. Further research is needed to explore spatial and temporal changes in dengue transmission to improve prevention and control efforts.